(untitled) (Revista de Ciências Agroveterinárias, 2017)
Varronia curassavica Jacq., black sage, is a medicinal plant with commercial interest due its anti-inflammatory properties. This species can be propagated by seeds, via vegetative propagation enabling the achievement of more uniform crops in relation to the agronomic and phytochemicals aspects. Thus, the present study aimed to evaluate the effect of different concentrations of indole butyric acid (IBA) and different leaf numbers in softwood stem cuttings of black sage plants. The experiment was conducted in august (winter season) in a factorial arrangement 3x2, with three different concentrations of IBA (0, 1500 and 3000 mg L-1) and two numbers of leaves (two leaves or one leaf). The experiment was conducted in a greenhouse under intermittent mist conditions. At 60 days after planting, the rooting percentage, number of roots per cutting, length of the three longest roots, percentage of cuttings with callus, percentage of live cuttings without roots nor callus, percentage of dead cuttings and percentage of cuttings with shoots were evaluated. There were significant differences for number of roots per cutting, which was higher at a concentration of 3000 mg L-1 compared to treatment without application of IBA (32.5%), and for percentage of cuttings with callus (15.0%), also higher were cuttings with two leaves at a concentration of 3000 mg L-1 IBA. For other factors there were no statistical differences between treatments. We conclude that the different number of leaves and IBA concentrations had little influence on the adventitious roots, mainly due to the winter season.